Enosmerni tok novic v vzvratnem ogledalu - Tomanić Trivundža, Ilija (Javnost (Ljubljana), 2015)
The article addresses the ongoing relevance of the MacBride report through the perspective of one of the key concerns voiced by the report - structural dominance of international news market that results in information dependency of developing countries and their consequent inability to achieve balanced and autonomous media representation. This question is addressed from a historical perspective through analysis of visual news reporting in three Yugoslav daily newspapers in 1988, which were part of the information system that aimed to balance the oneway fl ow of information. This analysis of visual coverage of international news - which shows that the representation of developing countries depends more on editorial independence than on structural inequality of the raw news - also fills a gap in existing research on international news within the context of NWICO debate which tends to neglect the visual modality of news reporting. It also off ers a starting point for critical appraisal of the normative demands put forward by the report within the context of contemporary global communication.
Keywords: časniki; informiranje; Jugoslavija; novinarstvo; politične razmere; tisk